2011
DOI: 10.1007/s00125-011-2194-5
|View full text |Cite
|
Sign up to set email alerts
|

The previously reported T342P GCK missense variant is not a pathogenic mutation causing MODY

Abstract: Abbreviations GCK Glucokinase SNP Single nucleotide polymorphismTo the Editor: There is renewed interest in the difficulties of interpreting the role of missense variants identified in large scale medical resequencing projects made possible by next generation sequencing technologies. To assist in ascribing a role in disease causation for these variants, a combination of statistics, bioinformatic tools and, ultimately, functional studies, will be needed. Missense variants identified in highly penetrant Mendelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…These studies have provided important insights into the structure and regulation of glucokinase and can provide additional confidence in the interpretation of the significance of a genetic variant in glucokinase (72). (Table 2 and Fig.…”
Section: Functional Analysis Of Gck Gene Mutationsmentioning
confidence: 99%
“…These studies have provided important insights into the structure and regulation of glucokinase and can provide additional confidence in the interpretation of the significance of a genetic variant in glucokinase (72). (Table 2 and Fig.…”
Section: Functional Analysis Of Gck Gene Mutationsmentioning
confidence: 99%
“…Steele and colleagues found that a heterozygous GCK missense variant, p.T342P, which was previously reported as pathogenic loss-of-function, neither demonstrated impaired catalytic activity nor cosegregation with the disease phenotype in the two families in which it was identified [95]. The variant was also classified as benign by three different in silico prediction tools, SIFT, Polyphen, and Mutation Taster [95]. The p.T342P substitution was not inherited by relatives with an overtly diabetic or elevated fasting glucose phenotype, and other relatives in whom the allele was identified were euglycemic (<5.5 mmol/l fasting glucose) [95].…”
Section: Using In Vitro Assays To Uncover the Functional Impact Of Mumentioning
confidence: 97%
“…Transparent reporting of findings is equally pivotal, as this allows medics and researchers to make independent interpretations and assessments of the published data and the way in which they were generated. Recent familial/functional studies on glucokinase have shown that analyzing variants, which were previously reported and characterized as pathogenic in this combinatorial manner, sometimes showed the opposite effect [94,95]. Steele and colleagues found that a heterozygous GCK missense variant, p.T342P, which was previously reported as pathogenic loss-of-function, neither demonstrated impaired catalytic activity nor cosegregation with the disease phenotype in the two families in which it was identified [95].…”
Section: Using In Vitro Assays To Uncover the Functional Impact Of Mumentioning
confidence: 99%
See 1 more Smart Citation
“…13 Benign, non-pathogenic sequence variants can be reported as MODY causing mutations and careful interpretation taking into account functional studies, segregation analysis, in silico predictions and frequencies according to geographic origin of the patients is required. 22 …”
Section: Analytical Specificity (Proportion Of Negative Tests If the mentioning
confidence: 99%